THE ESSENCE AND SIGNIFICANCE OF THE POETIC SIGN (The Conference Hub, 2026)
This article analyzes the discursive interpretation of poetic texts, focusing on their semantic and cognitive features. Poetic texts are connected with surrounding culture and other texts, allowing the formation of new meanings. The discursive approach examines the text through the “author–text–reader” relationship, emphasizing the importance of text creation and perception processes. The article also discusses the multiplicity of interpretations, cognitive-discursive factors, semantic and emotional components of poetic speech, zones of uncertainty, and their influence on reader activity. As a result, the polysemantic potential of poetic texts and the significance of interaction with the reader are highlighted.